INVESTIGATION INTO QUALITY FEATURES IN LACTOBACILLI CONCENTRATE THROUGH CRYO-FREEZING AND SUBLIMATION DRYING - Inna Kharitonova; Alexander Yu. Prosekov; Maria I. Shramko (Вестник Северо-Кавказского федерального университета, 2022)
The item offers the outcomes of a study into the comparative features of some of bacterial concentrates obtained in a conventional manner and granulated cryo-frozen bacterial concentrates. There is a view presented on the features of sublimation drying of bacterial concentrates.